Kajian Konsep Desain Interior Perpustakaan Di SMA Negeri 5 Bukittingi - Husnul Fadela; Heldi Heldi (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
The development of libraries has become part of the physical infrastructure of educational institutions. SMA Negeri 5 Bukittinggi needs infrastructure, library facilities as the heart of education. However, based on the initial survey and analysis, the shape of the elements is not yet optimal in maintaining the spatial concept of library interior design at SMA Negeri 5 Bukittinggi. Some indicators of spatial planning problems include interior design elements; floor, ceiling, lighting, coloring, furniture, air circulation, room circulation and acoustics. The aim of the research is to find out and identify the forms of replacement elements and identify the interior concept of the SMA Negeri 5 Bukittinggi library. The research method uses descriptive qualitative, observation analysis, survey and documentation approaches. Data was collected through interviews with 12 stakeholder sources. The findings show. The shape of the library interior design elements changes: floor; (30 x 30) cm, wall ; cream color, ceiling; white color, lighting; glass windows, air circulation; natural, room circulation; not optimal. The interior design concept applied originates from the needs of library staff and users and already meets the space requirements (including function, users, and expectations to be achieved from a spatial arrangement) but in general it needs to be developed according to the concept expected in the spatial layout. In arranging the library layout, it is necessary to pay attention to the elements, elements of spatial planning and the concept of applying interior design.